Beyond Simple Inoculation: Examining the Persuasive Value of Inoculation for Audiences with Initially Neutral or Opposing Attitudes. Issue 1 (1st January 2017) - Ivanov, Bobi; Rains, Stephen A.; Geegan, Sarah A.; Vos, Sarah C.; Haarstad, Nigel D.; Parker, Kimberly A.
Abstract : It is well established that—among individuals who hold an attitude toward a topic—inoculation messages can help promote resistance to counterattitudinal attacks. Yet, the utility of inoculation theory for communication campaigns may ultimately depend upon the effects inoculation messages have on individuals who are initially opposed or neutral regarding the topic. A three-phase experiment ( N = 282) was conducted to examine the effects of inoculation and supportive messages among individuals with neutral and opposing attitudes. The results revealed that, compared to the control groups, inoculation and supportive messages moved neutral and opposing attitudes in the message-advocated direction. Moreover, inoculation and supportive messages protected these attitudinal gains from attack-message-induced slippage. Since inoculation messages outperformed supportive messages, inoculation has potential utility for communication campaigns.